Dynamics of Legal Politics and Power Contestation after Constitutional Court Decision Number 60/PUU-XXII/2024 Concerning the Wholesale Party System in the 2024 Simultaneous Regional Elections - Yudhistira, Dhieno; Santiago, Faisal (Jurnal Greenation Sosial dan Politik, 2025)
Constitutional Court Decision Number 60/PUU-XXII/2024 has become a critical turning point in the Indonesian legal political landscape, especially regarding the political party system in the implementation of the 2024 Simultaneous Regional Elections. This decision cancels the practice of "wholesale parties" which allows political parties to lend candidacy tickets without substantive involvement in the political process, which has been considered to reduce the quality of democracy and local political accountability. The study analyzes the dynamics of legal politics that emerged after the decision, including the responses of political parties, and election organizers, and their impact on the map of power contestation in the regions. Through a juridical-political approach, this study explores how the Constitutional Court's decision affects the configuration of regional election law, opens up opportunities for party system reform, and at the same time, gives rise to resistance from political actors who have benefited from the practice of wholesale parties. The research results reveal that this decision is not only a correction to legal norms but also an intervention against the oligarchic structure in local democracy. However, the implementation and supervision of the effects of the decision still face challenges, especially in enforcing regulations and the consistency of their derivative regulations. Thus, the dynamics of post-decision legal politics show the tug-of-war between the interests of democratic reform and the power of the status quo in the local political system.